HUMAS SEBAGAI FASILITATOR KOMUNIKASI DALAM MENANGANI KELUHAN PELANGGAN WILAYAH SIDOARJO TERKAIT DITARIKNYA SUBSIDI LISTRIK 900 VA - Rochman, Taufiqur; Soenarjanto, Bagoes; Ekoputro, Widiyatmo (representamen, 2019)
The state electricity company is a state-owned enterprise engaged in the field of electricity. The state electricity company that deals with customer service, namely the distribution section. The state electricity company is an electricity industry that has the potential for people's lives. PT. The Sidoarjo regional electricity company is one of the state electricity companies engaged in the distribution of electricity for customer service management and electricity network services. However, recently there were customer complaints regarding the withdrawal of 900 VA electricity subsidies, this withdrawal was due to policies from the government which were considered to be inadequate to obtain electricity subsidies. Teratric researchers to examine this research because the case experienced just happened and the researchers wanted to know how the process carried out by PR in completing the case. From the study, it was adjusted the results that the poorer communities could still get electricity subsidies by submitting a certificate of incapacity from the kelurahan. This research method uses a qualitative approach and uses descriptive types of research. The literature review used is a functional approach using an open system model with a "two-way symmetrical" approach from the results of this study that public relations succeeded in carrying out its role as a communication facilitator.Keywords: Communication Facilitators, Public relations, Customer